Optimization of enzymatic hydrolysis of palm kernel expeller and its effect on broiler's growth performance - Chen, Wei Li; Jahromi, Mohammad Faseleh; Abdullah, Norhani; Idrus, Zulkifli; Liang, Juan Boo (Faculty of Animal Husbandry, Brawijaya University, 2017)
The effectiveness of enzymatic hydrolysis is dependent on various factors such as temperature and moisture content which influence the stability and functionality of enzymes. In this study, parameters influencing the enzymatic fermentation of palm kernel expeller (PKE) were optimized employing response surface methodology (RSM). In addition, the effectiveness of enzymatic treatment of PKE in improving its inclusion level in broiler diets was evaluated. The results showed that temperature, enzyme concentration and hydrolysis time had significant (P< 0.01) effect on the enzymatic hydrolysis of PKE. Using the crude enzyme produced by Aspergillus terreus K1, maximum reduction of crude fiber (40%) were achieved by fermenting the PKE at 60% initial moisture with 9.0 U/g PKE mannanase at 51 °C for 18 h. Results of the growth performance study showed an increase in FCR with increase in PKE inclusion level. However, increasing the inclusion rate of enzyme-treated PKE to 30% did not affect FCR of broilers as compared to those fed 20% PKE. Overall result of this study indicates that birds can be fed with 5% of PKE during the starter period and the PKE inclusion level can increase to 20% PKE in the finisher diet.